Analisi Peran Media Sosial Dalam Promosi Pariwisata - Shalsagiani, Auralia Intan; Suryasih, Ida Ayu (JURNAL DESTINASI PARIWISATA; Vol 11 No 2 (2023): VOL 11, NO 2 (2023): (JULY-DECEMBER) JURNAL DESTINASI PARIWISATADO - 10.24843/JDEPAR.2023.v11.i02.p04, 2023)
This research aims to analyze the role of social media, particularly through a study on the Bali Bird Park Instagram account, in tourism promotion. By utilizing Instagram, Bali Bird Park leverages captivating visual content to attract users attention and generate interest in visiting the bird park. This study highlights the importance of high-quality visual content, interaction with followers, collaboration with Influencers, consistency in content management, and understanding changes in algorithms, platform features, trends, and user preferences. The research method employed is a qualitative approach using descriptive analysis, which involves presenting data by explaining and providing an overview of the collected data, followed by drawing conclusions. Data collection techniques used in this research include observation, interviews, and documentation. The results of the study indicate that Instagram is a platform with various features for tourism promotion, but it also faces challenges such as limited organic reach, high competition, and changes in the social media environment. Keywords: Bali Bird Park, Tourism Promotion, Instagram